Peran Teknologi Pendidikan dalam Meningkatkan Mutu Pembelajaran di Era Digital: Penelitian - Afriantoni; Angel Rahmadani; Diah Puspita; Prima Sena Ardinata (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article investigates the role of educational technology in improving the quality of learning in Indonesian schools in the digital era. Using qualitative methods, this study collects data from various literature sources to understand the impact of existing educational technology and its potential to improve the learning process. The results show that educational technology plays an important role in supporting interactive learning, facilitating access to information, and improving the quality of learning. However, its implementation is faced with a number of challenges, such as limited infrastructure, costs, and teacher skills in using technology. To overcome these challenges, efforts are needed to ensure adequate access to technology, develop teacher skills, and create regulations that support the use of technology in education. Thus, it is hoped that concrete recommendations can be produced to improve the effectiveness and efficiency of learning through the use of educational technology.